Photovoice Handbook for Social Workers Method, Practicalities and Possibilities for Social Change - Jarldorn, Michele (Springer International Publishing : Imprint: Palgrave Pivot, 2019)
"In a thoroughly original approach, this book examines the benefits of using Photovoice as an emancipatory tool for community driven research. The strength of this book lies in the way it combines critical engagement with theory and the practicalities of using Photovoice to draw on the knowledge of marginalised members of communities whose voices have been silenced in many ways. A must read for all social workers." - Kathomi Gatwiri, Lecturer, School of Arts & Social Sciences, Southern Cross University, Queensland, Australia "Michele Jarldorn brings to life Photovoice as an intriguing method for social work research, especially for social workers with a critical standpoint. Photovoice is a qualitative, community-based, participatory action research method and Jarldorn illustrates its value with examples from her own research. At the heart of the discussion of this progressive method, Jarldorn places her deep commitment to the creative and transformative potential of Photovoice to actively involve participants in knowledge production." - Liz Beddoe, Associate Professor, School of Counselling, Human Services and Social Work, University of Auckland, New Zealand. This book provides inspiration for social workers to explore the possibilities of using Photovoice to engage with communities. Built on strong theoretical foundations and grounded in ethical principles, Jarldorn assesses Photovoice as an arts-based approach that provides a valuable mechanism for social workers to engage people in participatory action research, with the potential to influence policy and public opinion. Positioning Photovoice as a method aligned with feminist and radical social work perspectives, the author draws upon her research project which used Photovoice with former prisoners to demonstrate the transformative potential of participatory methods. Photovoice Handbook for Social Workers is intended to be a useful, hands-on resource, combining the importance of theory and the practicalities of doing action research. Michele Jarldorn is Associate Lecturer in Social Work, Flinders University, South Australia. .